2016
DOI: 10.1136/archdischild-2016-311436
|View full text |Cite
|
Sign up to set email alerts
|

Hyperhomocysteinaemia in children receiving phenytoin and carbamazepine monotherapy: a cross-sectional observational study

Abstract: Phenytoin or carbamazepine monotherapy for >6 months duration is associated with hyperhomocysteinaemia in 90% of North Indian children. Elevated homocysteine concentrations were normalised in these children with folic acid supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…[15,19,20] Three studies were performed in India. [21,22,23] One study was conducted in each of Turkey, [16] USA, [12] Korea, [24] and Germany. [11] Among included studies, 6 papers [15,16,19–21,22] reported the serum levels of all 3 parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[15,19,20] Three studies were performed in India. [21,22,23] One study was conducted in each of Turkey, [16] USA, [12] Korea, [24] and Germany. [11] Among included studies, 6 papers [15,16,19–21,22] reported the serum levels of all 3 parameters.…”
Section: Resultsmentioning
confidence: 99%
“…[21,22,23] One study was conducted in each of Turkey, [16] USA, [12] Korea, [24] and Germany. [11] Among included studies, 6 papers [15,16,19–21,22] reported the serum levels of all 3 parameters. One of them had levels of folate and vitamin B12 [11] and the 2 studies had the level of Hcy, [12,23] and the last one had solely level of Hcy and folate.…”
Section: Resultsmentioning
confidence: 99%
“…However, a decrease in MTHFR activity by phenytoin treatment at therapeutic plasma levels was observed in mice [21]. Enzyme-promoting AEDs such as phenytoin and phenobarbital are known to cause riboflavin and folate deficiencies via induction of cytochrome P450 [16, 22]. It has been reported that phenytoin decreases serum pyridoxal levels, leading to hyperhomocysteinemia [23].…”
Section: Discussionmentioning
confidence: 99%
“…After one year of sup plementation, the authors observed a significant de cline in the Beck Depression Inventory, in the hyper homocysteinemia, and in seizure frequency observed (Bochyńska et al 2012). In another study of children receiving carbamazepine and phenytoin treatment, supplementation with 5 mg/day folic acid for one month was associated with an increase in serum homocysteine levels, and a reduction in B 12 and folic acid levels (Chandrasekaran et al 2017). Supplementation was also associated with a reduction in plasma homocysteine concentrations in the study group (Chandrasekaran et al 2017).…”
Section: Introductionmentioning
confidence: 93%
“…In another study of children receiving carbamazepine and phenytoin treatment, supplementation with 5 mg/day folic acid for one month was associated with an increase in serum homocysteine levels, and a reduction in B 12 and folic acid levels (Chandrasekaran et al 2017). Supplementation was also associated with a reduction in plasma homocysteine concentrations in the study group (Chandrasekaran et al 2017). Given these results levels of vitamin B 6, vitamin B 12 , and folic acid should be monitored among patients receiving anticonvulsant drugs, and supplementation may be beneficial (Bochyńska et al 2012, Chandrasekaran et al 2017).…”
Section: Introductionmentioning
confidence: 95%